2015
DOI: 10.1007/s10815-015-0579-y
|View full text |Cite
|
Sign up to set email alerts
|

The original Beckman Coulter Generation II assay significantly underestimates AMH levels compared with the revised protocol

Abstract: Purpose Anti-Müllerian hormone (AMH) is used as a marker for ovarian reserve. Since 2011, the standard test for AMH has been the Beckman Coulter Generation (Gen) II assay. However, in July 2013, the protocol was revised due to falsely low readings. The aim of this study was to compare AMH levels measured with the original and revised Gen II assay and to establish a fertile female reference range for the revised protocol. Methods Serum AMH levels were measured for 492 natural conception first trimester pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…In July 2013, the Gen II assay protocol was revised to address concerns that results generated using an undiluted sample may potentially be falsely suppressed; fresh or freshly frozen specimens being particularly susceptible to complement interference. 26 Nevertheless, a recent study has demonstrated that AMH assay methods, manufactured by Beckman Coulter, Roche and Ansh Labs are well correlated. 27 A healthy cohort recruited from an annual heath screen enabled us to establish thresholds for testosterone, AFC and OV.…”
Section: Discussionmentioning
confidence: 99%
“…In July 2013, the Gen II assay protocol was revised to address concerns that results generated using an undiluted sample may potentially be falsely suppressed; fresh or freshly frozen specimens being particularly susceptible to complement interference. 26 Nevertheless, a recent study has demonstrated that AMH assay methods, manufactured by Beckman Coulter, Roche and Ansh Labs are well correlated. 27 A healthy cohort recruited from an annual heath screen enabled us to establish thresholds for testosterone, AFC and OV.…”
Section: Discussionmentioning
confidence: 99%
“…18 In 2010, Beckman Coulter combined these technologies to produce a second-generation (Gen II) AMH ELISA. 19 This assay was subsequently modified to minimize interference from complement [20][21][22] and has recently been adapted for the Beckman Access automated platform.…”
Section: Introductionmentioning
confidence: 99%
“…Serial incubation & washing with anti-AMH detection antibody, enzyme and substrate enables to determine the enzymatic turnover of the substrate that is directly proportional to the concentration of AMH in the serum. According to our reference interval, median AMH concentration for ages 20-24 was 2.42 ng/ml, ages 25-29 was 2.87 ng/ml, ages 30-34 was 2.49 ng/ml, ages 35-39 was 1.51 ng/ml [12].…”
Section: Amh Assaymentioning
confidence: 79%
“…On the same day (2 nd day) venous blood samples were collected from those subjects for the measurement of AMH level. Serum and plasma samples were centrifuged at 1700g within 2 hours from the collection time and stored at -80 º C until assayed [12].…”
Section: Amh (Anti-müllerian Hormone) Assaymentioning
confidence: 99%